Egg water from the amphibian Bufo arenarum induces capacitation-like changes in homologous spermatozoa - Krapf, Dario (2007)
Mammalian sperm acquire fertilizing capacity after residing in the female tract, where physiological changes named capacitation take place. In animals with external fertilization as amphibians, gamete interactions are first established between sperm and molecules of the egg jelly coat released into the medium. Since dejellied oocytes are not normally fertilized, the aim of this study was to determine if the jelly coat of the toad Bufo arenarum promotes a "capacitating" activity on homologous sperm. We found that sperm incubation in diffusible substances of the jelly coat (egg water) for 90-180 s is sufficient to render sperm transiently capable of fertilizing dejellied oocytes. The fertilizing state was correlated with an increase of protein tyrosine phosphorylation and a decrease of sperm cholesterol content. Inhibition of either the increase in tyrosine phosphorylation or cholesterol efflux affected the acquisition of fertilizing capacity. Phosphorylation and fertilization could be promoted with NaHCO3 and also by addition of beta cyclodextrin. Moreover, sperm could gain the ability to fertilize dejellied oocytes in the presence of these compounds. These data indicate that sperm should undergo a series of molecular changes to gain fertilizing capacity; these changes are reminiscent of mammalian sperm capacitation and take place before the acrosome reaction.